Single site metastatic rhabdomyosarcoma: an INternational Soft Tissue saRcoma ConsorTium (INSTRuCT) pooled analysis - Mercolini, Federico; Sparber-Sauer, Monika; Mascarenhas, Leo; Merks, Johannes H. M.; Koscielniak, Ewa; Heske, Christine M.; Chisholm, Julia; Coppadoro, Beatrice; Harrabi, Semi B.; Casey, Dana L.; Seitz, Guido; Dasgupta, Roshni; et al. (European journal of cancer, 2025)
Purpose - Although the prognosis for patients with metastatic rhabdomyosarcoma (RMS) is generally unfavorable, outcomes can vary significantly depending on the extent of metastatic spread. This study focuses on the specific subgroup of patients presenting with a single metastatic site, aiming to better define their clinical characteristics and outcomes. - Methods - Patients with a diagnosis of RMS and single-site metastatic involvement, collected in the INSTRuCT database were included. Clinical and pathological data were analyzed, with event-free survival (EFS) and overall survival (OS) as primary outcomes. - Results - Of 1095 metastatic patients, 497 (45.4%) had single-site metastasis: 187 in lung, 83 in distant lymph nodes, 72 in bone marrow, 53 in bone, and 102 in other sites. Most patients with lung-only metastasis had embryonal histology. Compared to patients with multiple metastatic sites (5-year EFS: 16.4%, 95%CI 13.5-19.6; OS: 19.8%, 95% CI 16.6-23.2), those with single-site metastasis had better outcomes, showing 5-year EFS of 39.7% (95% CI 33.7-42.4) and OS of 47.0%, (95% CI 42.4-51.5) with significant site differences: 5-year OS was 53.3% (95% CI 45.8-60.3) for lung, 49.2% (95%CI 37.2-60.2) for lymph nodes, and 53.0% (95%CI 42.6-62.4) for other sites, but only 33.5% (95%CI 20.2-47.3) for bone and 28.7% (95%CI 18.5-39.7) for bone marrow (p=0.0006). The presence of a fusion transcript negatively impacted prognosis for distant nodes (5-year EFS: 35.7% vs. 63.6%), lungs (10.0% vs. 49.5%), and other sites (13.6% vs. 65.5%). - Conclusion - Within the patients with metastatic RMS, those with distant tumor isolated in lung, lymph node, or 'other' sites are associated with lower risk of events, while bone and bone marrow metastasis indicate poorest prognosis. The fusion transcript plays an important role in specific subgroups.